SEMANTIC FEATURES OF PEDAGOGICAL TERMS - Malohat Odilova (Scholar Express Journal, 2022)
The emergence and practical use of new pedagogical terms is a widespread phenomenon. New terms also appear based on the internal resources of the language. This article analyzes semantic features of pedagogical terms.
Keywords: pedagogy; term; commonly used words; history of formation